2016
DOI: 10.1177/0897190016641491
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug Therapy-Related Issues in an Outpatient Heart Failure Population and the Potential Impact of Pharmacist-Driven Intervention

Abstract: The prevalence of DRI is high even among HF patients managed in a subspecialty cardiovascular practice. Pharmacists in this setting play a vital role in more effectively resolving DRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
2
19
3
1
Order By: Relevance
“…In addition to guideline‐recommended medications, patients with CHF receive often pharmacotherapy for frequent co‐morbidities leading to polypharmacy . Especially elderly patients with polypharmacy are at risk to experience DRPs like double medication, drug interactions, adverse drug reactions, or non‐adherence . Adverse drug events and therapy failure due to DRPs are potentially preventable by interdisciplinary efforts involving pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to guideline‐recommended medications, patients with CHF receive often pharmacotherapy for frequent co‐morbidities leading to polypharmacy . Especially elderly patients with polypharmacy are at risk to experience DRPs like double medication, drug interactions, adverse drug reactions, or non‐adherence . Adverse drug events and therapy failure due to DRPs are potentially preventable by interdisciplinary efforts involving pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist intervention by delivering pharmaceutical care in a multidisciplinary care team has been shown to improve clinical outcomes in a variety of patients with chronic diseases such as heart failure, hypertension, and diabetes. 9 11 As concerns psychiatric disorders, some clinical studies have addressed pharmaceutical care in psychiatric patients with depression and autism spectrum disorder. 12 , 13 The results also revealed that pharmacist intervention could help to improve clinical outcomes in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist interventions on outpatient prescriptions were rarely reported. Limited studies were restricted to certain type of outpatient prescriptions, such as prescriptions of pediatric patients [ 8 ], geriatric patients [ 9 ], emergency patients [ 10 ], patients undergoing oral chemotherapy [ 11 , 12 ] and those with heart failure [ 13 ]. These limited articles have all demonstrated that pharmacist intervention can reduce suboptimal prescriptions.…”
Section: Introductionmentioning
confidence: 99%